EPlantLIBRA: A composition and biological activity database for bioactive compounds in plant food supplements. (15th February 2016) - Plumb, J.; Lyons, J.; Nørby, K.; Thomas, M.; Nørby, E.; Poms, R.; Bucchini, L.; Restani, P.; Kiely, M.; Finglas, P.; ,
Highlights: The development of ePlantLIBRA a comprehensive web-based plant food supplement (PFS) database. A comprehensive and searchable database containing quality evaluated scientific information from over 570 publications included covering 70 PFS or their botanical ingredients. Data included on PFS health benefits, adverse effects and bioactives composition. Data included on botanical information, contaminants and residues. Valuable resource for food regulatory and advisory bodies, researchers and product developers. Abstract: The newly developed ePlantLIBRA database is a comprehensive and searchable database, with up-to-date coherent and validated scientific information on plant food supplement (PFS) bioactive compounds, with putative health benefits as well as adverse effects, and contaminants and residues. It is the only web-based database available compiling peer reviewed publications and case studies on PFS. A user-friendly, efficient and flexible interface has been developed for searching, extracting, and exporting the data, including links to the original references. Data from over 570 publications have been quality evaluated and entered covering 70 PFS or their botanical ingredients.